Diagnosing Innovation Challenges in Indonesian SMEs: A Bibliographic Analysis and Conceptual Framework for Strategic Intervention - Arenal Arenal; Henry Eryanto; Mardi Mardi (Interdisciplinary Social Studies, 2026)
Small and medium-sized enterprises (SMEs) in Indonesia are critical drivers of economic growth and employment, yet they face persistent innovation challenges that impede competitiveness. Structural, strategic, and geographical disparities across the archipelago limit SMEs’ ability to leverage external knowledge, engage in open innovation, and adopt digital transformation initiatives effectively. This study aims to diagnose key innovation barriers in Indonesian SMEs and develop a conceptual framework to guide strategic interventions. A systematic bibliographic analysis was conducted using 788 Scopus-indexed documents published between 2000 and 2025. Keyword co-occurrence, thematic mapping, and temporal overlay analyses were applied to identify the conceptual structure, thematic clusters, and evolutionary patterns in SME innovation research. The analysis highlighted seven critical challenges: limited absorptive capacity, low engagement in open innovation, misaligned business strategies, insufficient policy support, fragmented innovation networks, weak innovation culture and leadership, and ineffective benchmarking systems. Findings indicate that while foundational concepts such as performance and entrepreneurship are well-established, strategic mechanisms and digital transformation remain peripheral in both practice and literature. The study’s discussion emphasizes the need for integrated interventions across organizational, knowledge, and strategic execution levels. In conclusion, the proposed multi-level conceptual framework provides a diagnostic tool for policymakers and SME managers to identify bottlenecks, enhance innovation capacity, and strengthen regional competitiveness.